A rare occupation causing mesothelioma: mechanisms and differential etiology - Mastrangelo, Giuseppe; Fadda, Emanuela; Comiati, Vera; Dell'Aquila, Massimiliano; Zamprogno, Emanuele; Fedeli, Ugo; Bellini, Enrico (La Medicina del Lavoro, 2014)
Background: In a mesothelioma lawsuit, the Public Prosecutor commissioned an expert evidence on the legal accountability for the disease, because the patient experienced multiple exposures to asbestos in both occupational and environmental settings. Objectives: To collect information on asbestos exposure from all available sources and to quantify the contribution of each source of exposure as a percentage of the total risk. Methods: We retrieved information on jobs done and asbestos exposure from a work colleague and a database maintained by the National Institute for Insurance of Occupational Accidents/Diseases, respectively. Information on environmental exposure was searched through the scientific literature. The contribution of each source of exposure was quantified with a method of risk apportionment, taking into account time elapsed since first and last exposure, intensity and frequency of exposure and carcinogenic potency of asbestos fiber mix. Results: The subject worked in the maintenance of railway electrification system. The mechanical compression stress induced on the ballast during passage of trains released chrysotile (from fragmented stones) and crocidolite (through abrasive action of crushed gravel on the underbody of rolling stocks insulated with friable crocidolite). Despite the low cumulative exposure (about 2 ff×years/cc), 99% of the mesothelioma risk was attributable to the work done because of the high content of crocidolite of inhaled asbestos. Conclusions: The report of an uncommon source of occupational asbestos exposure and a scientifically based method to allocate mesothelioma risk among multiple exposure could help to recognize mesothelioma as occupational disease in the workers employed in maintenance of the railway electrification system under the Italian National Railways.